Adjuvant chemotherapy is associated with improved survival in patients with stage II colon cancer. Issue 21 (15th July 2016) - Casadaban, Leigh; Rauscher, Garth; Aklilu, Mebea; Villenes, Dana; Freels, Sally; Maker, Ajay V.
Abstract : BACKGROUND: The role of adjuvant chemotherapy in patients with stage II colon cancer remains to be elucidated and its use varies between patients and institutions. Currently, clinical guidelines suggest discussing adjuvant chemotherapy for patients with high‐risk stage II disease in the absence of conclusive randomized controlled trial data. To further investigate this relationship, the objective of the current study was to determine whether an association exists between overall survival (OS) and adjuvant chemotherapy in patients stratified by age and pathological risk features. METHODS: Data from the National Cancer Data Base were analyzed for demographics, tumor characteristics, management, and survival of patients with stage II colon cancer who were diagnosed from 1998 to 2006 with survival information through 2011. Pearson Chi‐square tests and binary logistic regression were used to analyze disease and demographic data. Survival analysis was performed with the log‐rank test and Cox proportional hazards regression modeling. Propensity score weighting was used to match cohorts. RESULTS: Among 153, 110 patients with stage II colon cancer, predictors of receiving chemotherapy included age <65 years, male sex, nonwhite race, use of a community treatment facility, non‐Medicare insurance, and diagnosis before 2004. Improved and clinically relevant OS was associated with the receipt of adjuvant chemotherapy in all patient subgroups regardless of high‐risk tumor pathologic features (poor or undifferentiated histology, <12 lymph nodes evaluated, positive resection margins, or T4 histology), age, or chemotherapy regimen, even after adjustment for covariates and propensity score weighting (hazard ratio, 0.76; P <.001). There was no difference in survival noted between single and multiagent adjuvant chemotherapy regimens. CONCLUSIONS: In what to the authors' knowledge is the largest group of patients with stage II colon cancer evaluated to date, improved OS was found to be associated with adjuvant chemotherapy regardless of treatment regimen, patient age, or high‐risk pathologic risk features. Cancer 2016;122:3277–3287 . © 2016 American Cancer Society . Abstract : In what to the authors' knowledge is the largest group of patients with stage II colon cancer evaluated to date, improved overall survival was found to be associated with adjuvant chemotherapy regardless of treatment regimen, patient age, or high‐risk pathologic risk features.